Efforts to Improve Learning Outcomes of Tiger Jumping in Floor Gymnastics through Demonstration Teaching Methods - Muhammad Dia; Afri Tantri; Dewi Maya Sari (Jurnal Mahasiswa Pendidikan Olahraga, 2020)
This study aims to determine the improvement of tiger jump learning outcomes through the application of teaching styles of demonstration teaching methods to class Xl MIA 1 SMA Negeri 3 Medan for the 2019/2020 academic year. This study was a student of class XI who became a sample with a total of 28 students who would be given action in the form of learning through the Application of the Demonstration Teaching Method towards the learning outcomes of floor gymnastics tiger jumping. The method used in this research is Classroom Action Research. To obtain the data in this study, a learning outcome test was carried out at the end of each cycle in the form of an application to assess the Learning Outcomes of Tiger Jumping, Floor Gymnastics. With the implementation of this research learning outcomes test is carried out for two weeks or two meetings. Data analysis was performed by data reduction and data exposure. Of the 28 students, there were 8 students (28.57%) who had reached the level of mastery learning with an average value of student learning outcomes of 55.17%. The results of the first cycle, there were 18 students (64.28%) of 28 students, who had reached the level of mastery learning with an average value of student learning outcomes 68.14%. In cycle II there are 25 students (89.28%) of 28 students who have reached the level of learning completeness with an average value of 79%. It can be seen that student learning outcomes from the initial test to cycle I and cycle II have increased, it can be said through the application of this demonstration teaching method can improve student learning outcomes.